THE MOST COMMON CONTRAINDICATIONS FOR REFRACTIVE SURGERY - Zivkovic, Maja; Zlatanovic, Marko; Zlatanovic, Nevena; Brzakovic, Mladen; Hristov, Aleksandra (Acta medicae Medianae, 2023)
The preoperative examination for refractive surgery is of extreme importance for ensuring optimal outcomes and preventing complications. Aim of this study was to point out the most common contraindications for refractive surgery, laser-assisted in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK). The study included patients in the process of preoperative examination for refractive surgery who underwent complete standard ophthalmic examinations, as well as corneal topography and ocular biometry. Additional examinations were performed in cases of suspected specific ocular or systemic disease. Out of 1,238 patients (646 males and 592 females; mean age 32±10.4 years), refractive surgery was performed in 743 patients (60%), LASIK 367 (30%) and PRK in 376 patients (30%). Refractive surgery was contraindicated in 327 patients (26%) while 102 patients cancelled surgery. The most common reasons for not performing surgery were irregular cornea in 106 patients (32%), too steep or too flat corneal curvature in 71 patients (22%), insufficient corneal thickness in 62 patients (19%), high myopia in 28 patients (9%), high hyperopia in 19 patients (6%), dry eye in 13 patients (4%), incipient cataract in 10 patients (3%) and less common ocular and systemic diseases in 18 patients (6%). According to obtained results, irregular corneal topography, corneal curvature and insufficient corneal thickness are the most common reasons for not performing refractive surgery.